The English Course sebagai Media Peningkatan Sumber Daya Manusia Warga Br. Babakan Canggu, Kuta Utara-Badung - I Made Juliarta (Warmadewa Press, 2021)
This community service activity aims to improve the quality of human resources which is carried out by means of English language training. This activity is packaged in the form of an English Course / basic English training. This program was initiated thanks to the collaboration between the educators themselves and the Br Babakan Canggu community, and the Canggu language consultant to prepare human resources who are ready to compete in the world of work in the current 4.0 era. This English course / training was held for 4 months in the Br. Babakan Canggu North Kuta, Badung. The persuasive method is applied in the learning process with this type of qualitative research. While the data collection method is based on observation by observing the phenomena that occur in the field. The training provided to the participants included basic level English language training and Indonesian language training for foreign speakers. All English language training participants were very enthusiastic in participating in the English training process which was held in collaboration with the language and community consultancy agency Br Babakan Canggu, North Kuta, Badung. The process of English training provided to Babakan, Canggu residents was based on sincere sincerity.